Pigeon pea (Cajanus cajan L.) and corn (Zea mays L.) biomass production for silage as a function of mechanized tillage systems (Research, Society and Development, 2020)
Mechanical soil management has a huge impact on early plant development and can promote effects at all stages of the silage forage production cycle. Thus, this work was conducted to verify if a mechanized system of soil preparation influences the accumulation of pigeon pea and corn biomass. The experiment was conducted at the farm school of Federal University of Mato Grosso do Sul, Faculty of Veterinary Medicine and Animal Science. The experimental delimitation chosen was randomized blocks, the treatments were two systems of tillage (conventional and reduced), associated to two crops (Cajanus cajan L., cv. BRS Mandarim e Zea mays L. hybrid TG Status). The cv. BRS Mandarim in conventional tillage system impacted higher biomass values. In addition, the same soil preparation system promoted oscillations between the crops (P